2018
DOI: 10.1002/hed.25450
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus and human papillomaviruses as favorable prognostic factors in nasopharyngeal carcinoma: A nationwide study in Finland

Abstract: Background Nasopharyngeal carcinoma (NPC) is related to Epstein‐Barr virus (EBV) in endemic areas; however, the role of viruses in nonendemic countries is unclear. Our nationwide study investigated the prevalence and prognostic significance of EBV and human papillomaviruses (HPVs) in Finnish NPC tumors. Methods We analyzed samples from 150 patients diagnosed between 1990 and 2009. Viral status was determined using EBV and HPV RNA in situ hybridizations, and p16 immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 48 publications
6
67
1
2
Order By: Relevance
“…The role of smoking as a risk factor has been examined in several studies in both, low incidence and endemic regions, and the risk associated with smoking has been shown to be higher in low incidence countries 11 . More recently, several studies also described human papillomavirus (HPV) as a risk factor for NPCs in low incidence regions, although the causal link remains under debate 12‐15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of smoking as a risk factor has been examined in several studies in both, low incidence and endemic regions, and the risk associated with smoking has been shown to be higher in low incidence countries 11 . More recently, several studies also described human papillomavirus (HPV) as a risk factor for NPCs in low incidence regions, although the causal link remains under debate 12‐15 …”
Section: Introductionmentioning
confidence: 99%
“…In OPCs, early antigen HPV serology (especially antibodies against the HPV16 oncoprotein E6) has been shown to be very strongly associated with molecularly defined HPV‐positive OPCs, both at diagnosis and prospectively 17,20,21 . HPV detection in NPCs has been limited to p16 immunohistochemistry (IHC) and HPV DNA detection by PCR or in situ hybridization (ISH) 12‐15 . Currently, no serological assay has been validated for detecting HPV‐positive NPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several viruses have been detected in head and neck squamous cell carcinoma (HNSCC) [1][2][3][4][5][6][7]. Their etiologic and prognostic role is of great interest in cancer prevention and new management practices including immunotherapy [8][9][10] and treatment de-escalation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…31 In a study from 2019, Ruuskanen et al demonstrated presence of EBV in 62%, and HPV in 14% of cases of nasopharyngeal carcinoma, without coinfection. 60 Drop et al reported HPV/EBV co-infection in cancer of the oropharynx, larynx, and oral cavity in 28.6%, 21.4%, and 50%, respectively. 61 However, most patients in this study also had classical risk factors (smoking and alcohol abuse) for developing oropharyngeal cancer, which also could influence susceptibility to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Co‐infection was not found in epithelial tumors of the head and neck by Atula et al, but could be seen in a study by Jiang et al in tonsillar cancer and cancer of the base of tongue in 25% and 70% of cases, respectively . In a study from 2019, Ruuskanen et al demonstrated presence of EBV in 62%, and HPV in 14% of cases of nasopharyngeal carcinoma, without co‐infection . Drop et al reported HPV/EBV co‐infection in cancer of the oropharynx, larynx, and oral cavity in 28.6%, 21.4%, and 50%, respectively .…”
Section: Discussionmentioning
confidence: 99%